Single versus Double Injection Techniques in Supraclavicular Brachial Plexus Block and the Role of Perfusion Index: A Narrative Review (Jurnal Anestesiologi dan Terapi Intensif, 2026)
Ultrasound-guided supraclavicular brachial plexus block (SCBPB) is a widely used regional anesthesia technique for upper extremity surgery; however, variability in block onset and success remains a clinical concern. Differences in injection strategies, particularly single versus double injection techniques, have been proposed to improve anesthetic spread and block reliability. In parallel, the perfusion index (PI), derived from pulse oximetry, has emerged as a potential objective and non-invasive indicator for early assessment of block success. This narrative review aims to synthesize current evidence comparing single and double injection techniques in supraclavicular brachial plexus block and to evaluate the clinical value of the perfusion index as an objective monitoring tool. A narrative literature search was conducted using PubMed, ScienceDirect, and Google Scholar with keywords related to supraclavicular brachial plexus block, injection techniques, and perfusion index, focusing on studies published between 2015 and 2025. The reviewed literature suggests that the double injection technique is generally associated with faster sensory and motor onset, longer block duration, and higher block success rates compared with the single injection approach, although it requires longer procedural time and may slightly increase the incidence of transient neurological symptoms. Studies assessing perfusion index consistently demonstrate a significant increase following successful blocks, often preceding conventional sensory and motor assessments, with reported threshold values showing high sensitivity and specificity despite variability among studies. Overall, double injection supraclavicular brachial plexus block appears to offer improved block characteristics, while perfusion index monitoring represents a promising, rapid, and objective adjunct for early block evaluation. Further studies integrating injection techniques with standardized perfusion index assessment are required to optimize clinical application.
Keywords: Brachial Plexus Block; Injections; Perfusion Index; Supraclavicular Region; Ultrasonography